2016
DOI: 10.1111/ped.13042
|View full text |Cite
|
Sign up to set email alerts
|

Extrapontine myelinolysis associated with severe hypernatremia in infancy

Abstract: Extrapontine myelinolysis (EPM) is an uncommon disorder in children, with few pediatric cases reported to date. We report the first case of an infant with EPM without central pontine myelinolysis (CPM) presenting with severe hypernatremia. On admission, the infant had impaired consciousness, mild dehydration, and severe hypernatremia (190 mmol/L). The following day, the patient developed abnormal involuntary movements. Brain magnetic resonance imaging (MRI) confirmed EPM without CPM. He recovered without seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…15,16 The presence of extensive changes, especially in the extrapontine structures, reflects the effect of severe hypernatremia and high osmolarity on the myelin. 17,18 The intraneuronal idiogenic osmoles' slow dissipation results in persistent water retention leading to neuronal and glial swelling with resultant cerebral swelling. 19 These osmotic changes also cause intramyelinic edema and splitting of myelin lamellae in the myelinated fibers, reflected radiologically as diffusion restriction and reduction in apparent diffusion coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The presence of extensive changes, especially in the extrapontine structures, reflects the effect of severe hypernatremia and high osmolarity on the myelin. 17,18 The intraneuronal idiogenic osmoles' slow dissipation results in persistent water retention leading to neuronal and glial swelling with resultant cerebral swelling. 19 These osmotic changes also cause intramyelinic edema and splitting of myelin lamellae in the myelinated fibers, reflected radiologically as diffusion restriction and reduction in apparent diffusion coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…[14] ODS usually occurs during the rapid correction of hyponatremia, whereas it rarely occurs in severe hypernatremia. [5][6][7][8] Experimental work in laboratory animals with induced hypernatremia has revealed cellular damage and myelinolysis. Acute hypernatremia is characterized by cellular dehydration due to a shift of water from the interstitial and intracellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Although it usually occurs during rapid correction of hyponatremia, ODS due to hypernatremia has been reported in several patients, mainly adults, who develop acute hypernatremia due to various etiologies [5–7] . Only few cases of ODS in infants have been reported [8] . Here, we present the case of an infant with ODS resulting from hypernatremia due to NDI.…”
Section: Introductionmentioning
confidence: 87%
“…However, it can be associated with many other disorders or an electrolyte imbalance in which sodium levels may be normal or even high. [2][3][4] In a large review, Singh et al 5 showed that the most common predisposing factor of CPM and EPM was hyponatremia (78%), and the most common presentation was encephalopathy (39%). Recognized predisposing factors include alcoholism, liver transplantation, malnutrition, and chronic debilitation states.…”
Section: Introductionmentioning
confidence: 99%